Gastric cancer screening : a systematic review - Lídia Maria Azevedo Faria (2020)
Background and Aims: Population-based gastric cancer (GC) screening is recommended in high-risk populations, although screening methods and intervals vary. In intermediate-risk populations, European Society of Gastrointestinal Endoscopy guidelines suggest that esophagogastroduodenoscopy (EGD) screening may be considered depending on resources. The aim of this study was to characterize GC screening programs worldwide. Methods: Studies regarding population-based GC screening were searched through MEDLINE and Scopus. Studies on symptomatic patients, premalignant lesions, hereditary GC and GC surveillance were excluded. The following outcomes were analysed: adherence rate, early-GC detection rate and GC detection rate. Additionally, a survey on digestive cancer screening was sent to Endoscopy/Gastroenterology societies. Results: 44 studies were included. Population-based screening by upper gastrointestinal series (UGIS) or EGD is offered in Japan and Korea, with adherence rates between 14.31-58.01% and 7.40-74.8%, respectively. Japan reported early-GC detection rates of 0.02-0.21% and 0.35-0.66% and detection rates of 0.05-0.52% and 0.40-0.87%, for UGIS and EGD, respectively. Korea reported an EGD early-GC detection of 0.22% and detection rates between 0.01-0.29% and 0.07-0.08%, for EGD and UGIS, respectively. China offers EGD screening, with an adherence rate of 18.41% and early-GC and detection rates of 0.23-0.67% and 0.09-0.85%, respectively. In Western, several screening methods were used in pilot studies. Regarding the survey, only Serbia and Sweden reported the existence of a screening program. Discussion: Mass screening for GC is available in Japan, Korea and China. Endoscopy-based programs seem to achieve higher early-GC and GC detection rates rather than UGIS, with variable adherence rates.